Inhibition of Human Prostate and Bladder Smooth Muscle Contraction, Vasoconstriction of Porcine Renal and Coronary Arteries, and Growth-Related Functions of Prostate Stromal Cells by Presumed Small Molecule Gαq/11 Inhibitor, YM-254890 - Tamalunas, Alexander; Wendt, Amin; Springer, Florian; Ciotkowska, Anna; Rutz, Beata; Wang, Ruixiao; Huang, Ru; Liu, Yuhan; Schulz, Heiko; Ledderose, Stephan; Magistro, Giuseppe; Stief, Christian G.; et al. (Frontiers in Physiology, 2022)
Introduction: Lower urinary tract symptoms involve benign prostatic hyperplasia and overactive bladder. Medical treatment includes reduction of prostate and detrusor smooth muscle tone, and prostate growth. Current medications are marked by high discontinuation rates due to unfavourable balance between efficacy and side effects, which are cardiovascular and include hypotension, due to vasorelaxation by anticontractile LUTS medications. Agonist-induced smooth muscle contractions are caused by activation of receptor-coupled G-proteins. However, little is known about receptor- and organ-specific equipment with G-proteins. With YM-254890, a small molecule inhibitor with presumed specificity for Gαq/11 became recently available. Here, we investigated effects of YM-254890 on prostate, bladder and vascular smooth muscle contraction, and on growth-related functions in prostate stromal cells. Methods: Contractions of human prostate and detrusor tissues, porcine renal and coronary arteries were induced in organ bath. Proliferation (EdU assay), growth (colony formation), apoptosis and cell death (flow cytometry), viability (CCK-8) and actin organization (phalloidin staining) were studied in cultured human prostate stromal cells (WPMY-1). Results: Contractions by α1-adrenergic agonists, U46619 and endothelin-1 were nearly completely inhibited by YM-254890 (30nM) in prostate tissues. Contractions by cholinergic agonists, U46619 and endothelin-1 were partly inhibited in detrusor tissues. Contractions by α1-adrenergic agonists, U46619 and endothelin-1 were strongly, but not fully inhibited in renal arteries. Contractions by cholinergic agonists were completely, but by U46619 and endothelin-1 only partly inhibited in coronary arteries. In WPMY-1 cells, YM-254890 caused breakdown of actin polymerization and organization, and obvious, but clearly limited decreases of proliferation rate, colony formation and viability, and slightly increased apoptosis. Conclusions: Intracellular post-receptor signaling pathways are shared by Gαq-coupled contractile receptors in multiple smooth muscle-rich organs, but to different extent. While inhibition of Gαq/11 causes actin breakdown, anti-proliferative effects were detectable but clearly limited. Together this may aid in developing future pharmaceutical targets for LUTS and antihypertensive medication.